Propuesta para actualización de banco didáctico para prácticas de transferencia de calor en la Universidad Antonio Nariño sede Cartagena (2020)
Laboratory Practices on heat transfer are a fundamental tool in the training of Electromechanical engineers. Currently, the UAN Cartagena Campus does not have the appropriate experimental/didactic bank to carry out laboratory practices in tube and shell exchangers. This project aims to carry out the diagnosis and adaptation of a didactic shell and tube heat exchanger that has faults in its operation. The above, for the development of future laboratory practices and strengthening the training of the UAN Electromechanical engineer with the CDIO methodology.